2021
DOI: 10.1007/s00426-021-01610-6
|View full text |Cite
|
Sign up to set email alerts
|

Return-sweep saccades in oral reading

Abstract: Recent research on return-sweep saccades has improved our understanding of eye movements when reading paragraphs. However, these saccades, which take our gaze from the end of one line to the start of the next line, have been studied only within the context of silent reading. Articulatory demands and the coordination of the eye–voice span (EVS) at line boundaries suggest that the execution of this saccade may be different in oral reading. We compared launch and landing positions of return-sweeps, corrective sac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 59 publications
2
7
0
Order By: Relevance
“…Past studies have already shown subtle differences in return‐sweep behaviour when reading silently and aloud (i.e. Adedeji et al, 2021), so it remains an open question of whether the position of words will differentially affect fixations falling adjacent to return‐sweeps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past studies have already shown subtle differences in return‐sweep behaviour when reading silently and aloud (i.e. Adedeji et al, 2021), so it remains an open question of whether the position of words will differentially affect fixations falling adjacent to return‐sweeps.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed an effect of our manipulation on return-sweep fixations. Line-final fixations have consistently been reported to be shorter than intra-line reading fixations (Abrams & Zuber, 1972;Adedeji et al, 2021;Parker, Nikolova, et al, 2019;. It has been argued that this reflects reduced lexical processing during line-final fixations while readers prioritise oculomotor programming (Kuperman et al, 2010).…”
Section: Return-sweep Fixationsmentioning
confidence: 99%
“…We should also consider the relationship between intra-line fixations and return-sweep fixations. In the reading of alphabetic languages, it is well documented that, compared to intra-line fixations, line-final fixations are shorter, accurate line-initial fixations are longer and undersweep-fixations are shortest (Abrams & Zuber, 1972 ; Adedeji et al, 2022 ; Hawley et al, 1974 ; Heller, 1982 ; Hofmeister et al, 1999 ; Parker et al, 2020 ; Parker & Slattery, 2019 ; Rayner, 1977 ; Rayner, 1978 ; Slattery & Parker, 2019 ). We have no empirical grounds to anticipate that this basic pattern of effects might differ between alphabetic languages and character-based languages, and therefore, we expect that in the reading of Chinese multi-line texts, we might obtain the same pattern of results.…”
Section: Introductionmentioning
confidence: 99%
“…Return sweeps have been reported to undershoot their target on 40-60% of occasions and require an immediate corrective saccade towards the left margin (Slattery & Vasilev, 2019). The rate of undershoot error is again determined by characteristics of the text, such as line length (e.g., Parker & Slattery, 2021), but also by characteristics of the reader (i.e., reading skill; Parker & Slattery, 2021) or task demands (Adedeji et al, 2021). Due to the two trajectories of return-sweeps, the fixations following a return-sweep can be grouped into two fixation populations: accurate line-initial fixations (where the line initial fixation is followed by a rightwards saccade) and under-sweep fixations (where the line-initial fixation is followed by a leftwards saccade prior a rightwards pass).…”
mentioning
confidence: 99%
“…There is ample evidence to suggest that line-initial fixations are longer than intra-line reading fixations (Adedeji et al, 2021;Parker, Nikolova, et al, 2019;Parker & Slattery, 2021;Vasilev et al, 2021), presumably because readers are unable to engage in parafoveal processing for line-initial words and must complete word identification under foveal processing. In contrast, under-sweep fixations are shorter than intra-line reading fixations (Adedeji et al, 2021;Parker, Nikolova, et al, 2019;Parker & Slattery, 2021;Vasilev et al, 2021). It has been argued that these fixations are shorter as they are terminated based on retinal feedback and redirect a reader's gaze to a new position for lexical processing (Abrams & Zuber, 1972).…”
mentioning
confidence: 99%